Traumatic presentation of a solid pancreatic pseudopapillary neoplasm in a 7 year old girl - Jawad Ali; Julie Sanchez; Chandra Krishnan; Stephanie Streufert; Karla Lawson (Elsevier, 2015)
Solid pseudopapillary neoplasms of the pancreas are rare tumors that present in adolescence after having grown to a large size. We present the case of a young girl who had emesis and abdominal pain after hitting her abdomen on the side of her bathtub. She underwent workup and successful surgical resection in the same admission. In reviewing the literature, these tumors often present with a palpable mass or abdominal pain. They are diagnosed with various imaging modalities and have an excellent prognosis with complete surgical resection. Chemotherapy is reserved for unresectable or metastatic disease. The young age and traumatic presentation make this a notable case.